Revisiting the original Akin technique: A comparative analysis of radiographic outcome. Issue 3 (April 2022) - Dellonder-Frigolé, Josep; Matas-Pareja, Mariano; Calle-García, Juan-Antonio; Bowen, Jonathan; Fatjó-Rios, Jaume; Albertí-Fitó, Glòria
Highlights: Exists controversy about which is the best osteosynthesis device to stabilize an Akin osteotomy. Comparison of staple stabilization of the Akin osteotomy and no stabilization of the osteotomy. The use of staple to stabilize the osteotomy would not result in better postoperative radiological outcomes. Binary logistic regression model showed that poor HVA outcome was related with staple use (OR 3.547). Those patients where a staple was applied showed worse radiological results than those where no fixation was used. Abstract: Background: The Akin osteotomy is widely used to correct the hallux valgus and different fixation techniques have been proposed. Currently most of these procedures coexist, with disagreement on which offers the best results. The aim of this study is to compare the radiological outcome of the original Akin's technique with one in which a staple was used to stabilize the osteotomy. We also assessed whether other factors unrelated to the osteosynthesis could influence the radiological outcome. Methods: We retrospectively reviewed data from 118 patients who underwent a scarf and Akin osteotomy. In 60 patients the Akin osteotomy was fixed with a staple and in 58 cases no staple was used. Hallux valgus angle (HVA), distal articular set angle (DASA), interphalangeal angle (IPA) and tibial sesamoid position were measured. The presence of lateral cortex disruption of the phalanx was also included in the analysis. Results: Six variables significantly influenced the radiological results of the Akin osteotomy: preoperative HVA, IPA and tibial sesamoid position, laterality, postoperative cortical disruption and use of a staple. Conclusion: Ours results suggest that the original Akin's technique seems to offer equal or better results than a variation in which a staple is added to stabilize the osteotomy. Level of evidence: This is a level III retrospective case-control study.